Produksi Ujaran Fonologis Pada Anak Usia Dua Tahun Tiga Bulan Dalam Pemerolehan Bahasa Pertama - La Muda; Ella Ella; Waode Nur Maulid Sakti Basri; Widyanti Saputri (Jurnal Sultra Elementary School, 2026)
This study aims to describe phonological speech production and identify phonological deviations in a two-year-three-month-old child during first language acquisition. This research employed a qualitative approach using a naturalistic single-case study. The participant was a two-year-three-month-old child observed for one month across various interactional contexts, including home and school environments. Data were collected through observation, note-taking, and speech recording. The collected utterances were transcribed and analyzed by comparing the child's productions with corresponding adult speech forms as references. The data were subsequently classified into four phonological deviation patterns: substitution, deletion, assimilation, and reduplication. The analysis of 10 speech data revealed three types of phonological deviations: substitution, deletion, and a combination of substitution and deletion. Substitution was the most dominant pattern, particularly the gliding of /r/ and /l/ into sounds that were easier for the child to produce. Deletion of certain consonants was also identified, along with the occurrence of multiple phonological processes within a single word. Meanwhile, assimilation and reduplication patterns were not explicitly identified in the analyzed data. These findings indicate that phonological deviations are part of the child's developing articulatory abilities and occur systematically in relation to the complexity of the sounds being produced. The study contributes to understanding early phonological development in first language acquisition.